KEANEKARAGAMAN LAMUN (SEAGRASS) DI PERAIRAN PANTAI PASIR PUTIH KABUPATEN MANOKWARI, PAPUA BARAT - Balandina Selfina Awom; Selfani Talakua; Philipus Musyeri; Duijesisca Gultom (Yayasan Nusantara Hasana Berdikari, 2023)
Seagrass is a plant that lives in shallow seas with various different types of substrate and seagrass is a type of plant that has flowers, leaves and fruit. Manokwari City is one of the capital cities of West Papua Province which has waters, one of which is Pasir Putih waters. The diversity of seagrass species in this location is not yet well known, for this reason it is necessary to conduct research regarding the diversity of seagrass in the waters of Pasir Putih, Manokwari, West Papua. This research was conducted in July using the quadrant transect method. Based on research results, the types of seagrass found around the waters of white sand beaches consist of 4 types, namely Cymodocea rotundata, Halophila ovalis, Halodule pinifolia and Syringodium isoetofolium. The highest density of seagrass species is the Syringodium isoetifolium type with a value of 958 stands/m2, the highest relative density is the Syringodium isoetifolium seagrass type with a density percentage of 54%. The highest relative frequency is the seagrass species Halophila ovalis with a percentage of 34%. The level of diversity of seagrass species in transect I is in the medium group and in transects II and III is in the low group. The highest uniformity index value in transect I was 0.82 and the dominance index can be concluded that there is no type of seagrass that dominates the community.